2017
DOI: 10.1016/j.dld.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

The impact of acid suppression medications and non-steroidal anti-inflammatory drugs on clinical and histologic features in celiac disease

Abstract: Introduction The prevalence of celiac disease (CD) in the US has increased in past decades, as has use of proton pump inhibitors (PPIs), histamine-2-receptor antagonists (H2RAs), aspirin (ASA) and nonsteroidal anti-inflammatory drugs (NSAIDs). We aimed to measure the association between medication use and distribution of villous flattening (VF) among newly diagnosed CD patients. Methods We performed a cross-sectional study of adult patients with newly-diagnosed CD at two institutions. We collected data on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…After assessing the full texts of the 46 journal articles based on above-mentioned inclusion and exclusion criteria, a total of 16 studies were included in the final analysis. 13,15,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] Out of these, 12/16 were prospective studies. 13,15,26,27,29,[33][34][35][36][37][38] The schematic diagram of the screening and final selection of studies is shown in Supplementary Figure 1, Supplemental Digital Content 1, http:// links.lww.com/JCG/B4.…”
Section: Search Results and Population Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…After assessing the full texts of the 46 journal articles based on above-mentioned inclusion and exclusion criteria, a total of 16 studies were included in the final analysis. 13,15,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] Out of these, 12/16 were prospective studies. 13,15,26,27,29,[33][34][35][36][37][38] The schematic diagram of the screening and final selection of studies is shown in Supplementary Figure 1, Supplemental Digital Content 1, http:// links.lww.com/JCG/B4.…”
Section: Search Results and Population Characteristicsmentioning
confidence: 99%
“…Of the 114 studies that were initially felt to be appropriate, 68 were conference abstracts, which were excluded from the final analysis. After assessing the full texts of the 46 journal articles based on above-mentioned inclusion and exclusion criteria, a total of 16 studies were included in the final analysis 13,15,26–39 . Out of these, 12/16 were prospective studies 13,15,26,27,29,33–38 .…”
Section: Resultsmentioning
confidence: 99%